Q : skills for success. Reading and writing. 3 - Ward, Colin S.; Gramer, Morgot F. (New York: Oxford University Press, 2015)
This series that helps students to think critically and succeed academically. With new note-taking skills, an extended writing syllabus and authentic video in every unit, this book equips students for academic success better than ever. This book helps students to measure their progress, with clearly stated unit objectives that motivate students to achieve their language learning goals. Seamlessly integrated online content allows teachers to truly implement blended learning into the classroom
1
Keywords: English language -- Textbooks for foreign speakers; English language -- Composition and exercises; English language -- Rhetoric -- Study and teaching -- Foreign speakers; English language -- Study and teaching -- Foreign speakers; English language -- Web-based instruction